Production of fusion m13 phage bearing the di-sulphide constrained peptide sequence (C-WSFFSNI-C) that interacts with hepatitis B core antigen - Tey, Beng Ti; Ooi, Shin Tean; Yong, Khang Chi; Ng, Michelle Yeen Tan; Ling, Tau Chuan; Tan, Wen Siang (Academic Journals, 2009)
Effects of pH, temperature, and level of mixing on the production of fusion M13 phage bearing the peptide sequence (C-WSFFSNI-C) that interacts with HBcAg were investigated in this study. The optimum pH for the phage production was achieved at pH 7, followed by pH 6 and 8. The highest fusion phage titre was obtained at growth temperature of 37°C, followed by 27 and 42°C. The rotational speed at 250 rpm was the optimal mixing level for the phage production. Further increase of rotational speed to 300 rpm has reduced the phage production to a level lower than that obtained at 200 rpm. The results also showed that the propagation of fusion M13 phage has greatly affected the growth of Escherichia coli ER 2738. The viability of the phage produced with the current method was then determined using phage titre and dot-blot assays.